Finerenone Ameliorates High Glucose-Induced Podocytes Epithelial-Mesenchymal Transition Through the Regulation of Krüppel-Like Factor 5 in Diabetic Nephropathy - Shu J; Chen D; Chen W; Zhang X; Wang S; Chong N; Sun Z; Wang Q; Sun J; Xu Y (Diabetes, Metabolic Syndrome and Obesity)
Jianqiang Shu,1 Dandan Chen,1 Wenzhen Chen,2 Xinyu Zhang,1 Simeng Wang,1 Nannan Chong,3 Zhikang Sun,3 Qinglian Wang,3 Jingshu Sun,4 Ying Xu1 1Department of Nephrology, Shandong Provincial Hospital, Shandong University, Jinan, Shandong, People’s Republic of China; 2Clinic Medical College, The Second Hospital of Shandong University, Jinan, Shandong, People’s Republic of China; 3Department of Nephrology, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People’s Republic of China; 4Department of Nephrology, Weifang People’s hospital, Weifang, Shandong, People’s Republic of ChinaCorrespondence: Ying Xu, Department of Nephrology, Shandong Provincial Hospital, Shandong University, Jinan, Shandong, People’s Republic of China, Email 15562450030@163.comIntroduction: Diabetic nephropathy (DN) could impair the function of the glomerular filtration barrier by damaging the podocytes. Extant research has demonstrated that aldosterone plays a crucial role in this progression. Finerenone is a novel, high-selective mineralocorticoid receptor antagonist that has been demonstrated to be efficacious in renal protection in DN patients, albeit with an unclear underlying mechanism.Methods: Podocytes were stimulated with RPMI 1640 medium containing different concentrations of glucose and treated with finerenone to evaluate the protective effect of finerenone on podocytes in high glucose environment. Intraperitoneal injection of STZ was used to induce diabetic nephropathy rats and intragastric administration with finerenone or vehicles, and the changes of renal function, renal pathological changes and renal tissue protein expression were assayed.Results: Cell experiment showed that high glucose could induce epithelial–mesenchymal transition (EMT). After finerenone treatment, we accessed the EMT-related protein and found EMT was reversed. Besides, the cell migration capacity and cytoskeleton were also ameliorated. To further explore the mechanism, we found that finerenone could upregulate the expression of Krüppel-like factor 5 (KLF5) which was downregulated in a high glucose environment. After the silence of KLF5 in the presence of finerenone, the rescue experiment showed the protective function of finerenone is counteracted by KLF5. In animal experiment, after the treatment of finerenone, the level of blood creatinine decreased compared with the DN group while blood urea nitrogen (BUN) and potassium showed no significant difference. The pathological alterations of the treatment group also got ameliorated. Finerenone could normalize the level of EMT-related protein, nephrin, and KLF5 of kidney tissue in DN rats.Conclusion: Our results suggest that finerenone could alleviate high glucose-induced podocyte EMT via regulating KLF5. Further investigation is warranted to elucidate the precise underlying mechanism.Keywords: finerenone, DN, EMT, KLF5